2001
DOI: 10.1242/jcs.114.24.4567
|View full text |Cite
|
Sign up to set email alerts
|

Distinct functional domains in emerin bind lamin A and DNA-bridging protein BAF

Abstract: Loss of emerin, a lamin-binding nuclear membrane protein, causes Emery-Dreifuss muscular dystrophy. We analyzed 13 site-directed mutations, and four disease-causing mutations that do not disrupt emerin stability or localization. We show that emerin binds directly to barrier-to-autointegration factor (BAF), a DNA-bridging protein, and that this binding to BAF requires conserved residues in the LEM-motif of emerin. Emerin has two distinct functional domains: the LEM-domain at the N-terminus, which mediates bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 280 publications
(62 citation statements)
references
References 32 publications
3
57
2
Order By: Relevance
“…Thus, BAF is a key NE localization factor for both emerin and lamin A post-mitotically [52]. Together, these finding indicate that the recruitment and retention of emerin may involve sequential interactions with BAF and lamins [52].…”
Section: Emerin Domain and Structurementioning
confidence: 74%
See 4 more Smart Citations
“…Thus, BAF is a key NE localization factor for both emerin and lamin A post-mitotically [52]. Together, these finding indicate that the recruitment and retention of emerin may involve sequential interactions with BAF and lamins [52].…”
Section: Emerin Domain and Structurementioning
confidence: 74%
“…Recent studies have also suggested that BAF may be critically important for emerin NE localization, as emerin and lamin A both fail to associate with assembling nuclear envelope in cells that express a dominant mutant of BAF [52]. Thus, BAF is a key NE localization factor for both emerin and lamin A post-mitotically [52]. Together, these finding indicate that the recruitment and retention of emerin may involve sequential interactions with BAF and lamins [52].…”
Section: Emerin Domain and Structurementioning
confidence: 91%
See 3 more Smart Citations